2001
DOI: 10.1063/1.1396846
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of particle-laden turbulent channel flow

Abstract: This paper presents results for the behavior of particle-laden gases in a small Reynolds number vertical channel down flow. Results will be presented for the effects of particle feedback on the gas-phase turbulence and for the concentration profile of the particles. The effects of density ratio, mass loading, and particle inertia will be discussed. The results were obtained from a numerical simulation that included the effects of particle feedback on the gas phase and particle-particle collisions. The resoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
190
6

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 183 publications
(214 citation statements)
references
References 23 publications
(23 reference statements)
18
190
6
Order By: Relevance
“…It is well known that small heavy particles with large Stokes number dampen turbulence (Tsuji, Morikawa & Shiomi 1984;Gore & Crowe 1989;Hetseroni 1989;Elghobashi & Truesdell 1993;Kulick, Fessler & Eaton 1994;Li et al 2001;Yamamoto et al 2001;Ferrante & Elghobashi 2003;Mito & Hanratty 2006;Vreman 2007). In their experiments on particle-laden plane channel flow, Kulick et al (1994) reported a strong attenuation of the air turbulence intensity at low solid volume fraction but significant solid mass loading.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…It is well known that small heavy particles with large Stokes number dampen turbulence (Tsuji, Morikawa & Shiomi 1984;Gore & Crowe 1989;Hetseroni 1989;Elghobashi & Truesdell 1993;Kulick, Fessler & Eaton 1994;Li et al 2001;Yamamoto et al 2001;Ferrante & Elghobashi 2003;Mito & Hanratty 2006;Vreman 2007). In their experiments on particle-laden plane channel flow, Kulick et al (1994) reported a strong attenuation of the air turbulence intensity at low solid volume fraction but significant solid mass loading.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, if p-w collisions are included, it seems appropriate to include also p-p collisions in simulations of this type, although the overall particle volume fraction is low. Others have shown that p-p collisions significantly flatten the mean particle velocity profile and the mean particle volume fraction velocity profile at low volume fractions (Li et al 2001;Yamamoto et al 2001;Vreman 2007;Nasr et al 2009). At larger volume fractions p-p collisions were shown to enhance the transfer from the kinetic energy in the streamwise particle velocity fluctuations to the kinetic energy in both the normal and spanwise particle velocity fluctuations (Vreman et al 2009).…”
Section: −1mentioning
confidence: 99%
See 3 more Smart Citations